Psyllium Arabinoxylan: A Versatile Biomaterial for Potential Medicinal and Pharmaceutical Applications. (2nd January 2016) - Hussain, Muhammad A.; Muhammad, Gulzar; Jantan, Ibrahim; Bukhari, Syed Nasir Abbas
Abstract : Psyllium (PS), a water-swellable dietary fiber from seeds of widely distributed plant, Plantago ovata (PO) is esteemed for its medicinal and nutraceutical values. PS has been attributed to its broad range of pharmacological activities like anti-tumor, anti-inflammatory, anti-diabetic, hypolipidemic, laxative, anti-obesity, anti-diarrheal, anti-amoebic, and anti-nociceptive, and has been employed for sustained/delayed/targeted drug delivery due to its biocompatible and biodegradable nature. Interestingly, PS can be utilized for the absorption of toxic materials from industrial waste and is also used as substituent of gluten in breads for better acceptance. This review focuses upon the utilization of PS in drug delivery systems, medicinal uses, and pharmacological attributes to explore its potential in the nutraceutical industry.